EFEKTIVITAS PEMBELAJARAN MATEMATIKA MELALUI PENGGUNAAN MEDIA KOTAK BERHITUNG PADA SISWA KELAS II SD NEGERI 101 INPRES PATTALLASSANG - Mirdayanti; Mutmainnah, Ernawati (STKIP Subang, 2025)
The purpose of this study was to determine the effectiveness of the use of the Counting Box (KOBER) media in improving the mathematics learning outcomes of grade II students of SD Negeri 101 Inpres Pattallassang. The main problem in mathematics learning in elementary schools is the low learning outcomes of students due to monotonous learning methods and the lack of concrete media that attract students' attention. The research method used is a quantitative approach with a pre-experimental design of the one group pretest-posttest type. The research sample consisted of 25 grade II students. The research instruments included learning outcome tests, student activity observation sheets, and student response questionnaires. The results of the analysis showed a significant increase in student learning outcomes after the use of the KOBER media with a normalized gain value reaching 0.8 (high category). Student activities during learning were classified as active and student responses to the media were classified as positive. These results indicate that the Counting Box (KOBER) media is effective for use in mathematics learning in elementary schools, especially in multiplication operations.